The AMBU® Aura-i™ Laryngeal Mask and LMA Supreme™: A Randomized Trial of Clinical Performance and Fibreoptic Positioning in Unparalysed, Anaesthetised Patients by Novices - Zanahriah Yahaya; Wendy H. Teoh; Nora A. Dintan; Ravi Agrawal (Anesthesiology Research and Practice)
Introduction. Manikin studies’ data cannot accurately be extrapolated to real-life scenarios and inherent differences in design and materials of newer products may affect their clinical performance. Methods. Hence, we compared the AMBU® Aura-i™ and LMA Supreme™ in this randomized trial involving 100 ASA 1-2 unparalysed anaesthetised patients undergoing minor gynaecological surgery. Investigators had <20 Aura-i insertions. Primary outcome was time to achieve effective ventilation and secondarily insertion parameters, oropharyngeal leak pressures (OLP), fibreoptic positioning, and pharyngeal morbidity. The position of the Ambu Aura-i was evaluated with the Ascope; the fiberoptic view of the glottis was scored on a five-point scale. Results. 43 (86%) AMBU Aura-i and 44 (88%) LMA Supremes were successfully inserted on first attempt (p=0.59), with similar ease (p=0.79), and comparable times to first capnogram, mean (SD) 18.2 (6.0) versus 17.3 (6.4) sec, p=0.9. The Aura-i needed significantly less volume of air to inflate its cuff to 60 cmH2O on the manometer, 17.7 (3.5) versus 23.1 (4.4) mL, p<0.001. Both devices exhibited similar OLP, Aura-i versus LMA Supreme, mean (SD) 28.8 (7.1) versus 27.3 (5.3) cmH2O, p=0.24. There was no difference in ease of insertion or adjustment manoeuvres to aid ventilation. 90% of patients had good positioning of Aura-i on fibreoptic check, yielding a view of the vocal cords and epiglottis. In 5 patients (10%), the vocal cords were not seen, but ventilatory function was unaffected. Conclusions. The Aura-i handled well in novices hands, with comparable times to insert and establish ventilation, similar leak pressures, and successful first attempt insertion rates compared to the LMA Supreme.